The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1755-3768.2009.3113.x
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless encircling band – biomechanical calculations and clinical experience

Abstract: Purpose In cases with multiple retinal breaks and in combination with vitrectomy in eyes with Proliferative vitreoretinopathy (PVR) for retinal detachment surgery often an encircling band is used. Usually the encircling band is fixed with non absorbable sutures. Methods A fixation method for an encircling band in retinal detachment surgery with one scleral tunnel in every of the 4 quadrants is reported. We describe our experience and biomechanical calculations of this fixation technique. Results In compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Belt buckling leads to elongation of the optical axis, which in turn creates myopic shift and reduces tractional forces to ensure refraction with SOT. [ 4 6 ] A higher-viscosity SO has been reported to have a lower tendency to emulsify. [ 8 ] Moreover, the SO causes a change in refraction around 6D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Belt buckling leads to elongation of the optical axis, which in turn creates myopic shift and reduces tractional forces to ensure refraction with SOT. [ 4 6 ] A higher-viscosity SO has been reported to have a lower tendency to emulsify. [ 8 ] Moreover, the SO causes a change in refraction around 6D.…”
Section: Discussionmentioning
confidence: 99%
“…As SO does have a higher refractive index (1.405) than the vitreous humor (1.336), it causes a substantial variation in refraction when it is introduced into the vitreous cavity. [ 3 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…Refraktive Veränderungen sind unmittelbar auf den einschnürenden Effekt zurückzuführen. Das Ausmaß der Myopisierung ist von der Spannung und damit dem eindellenden Effekt der Cerlage abhängig [6,14]. Die myopisierende Wirkung ist bei gleicher Cerclagespannung allerdings bei der Skleratunnelfixation geringer [6,13].…”
Section: Abstract !unclassified
“…Das Ausmaß der Myopisierung ist von der Spannung und damit dem eindellenden Effekt der Cerlage abhängig [6,14]. Die myopisierende Wirkung ist bei gleicher Cerclagespannung allerdings bei der Skleratunnelfixation geringer [6,13]. Postoperativ kann es zur Erosion oder Intrusion des Cerclageelements kommen [7,10,14].…”
Section: Abstract !unclassified
“…Buckling elements are typically affixed to the sclera using nonabsorbable suture material such as mersilene, prolene or nylon. Other authors have demonstrated alternate means of hardware fixation including sclera tunnels and glue (Ricci & Ricci 2001 and Maier et al. 2011).…”
mentioning
confidence: 99%